2017
DOI: 10.1128/iai.01050-16
|View full text |Cite
|
Sign up to set email alerts
|

Eyedrop Inoculation Causes Sublethal Leptospirosis in Mice

Abstract: Leptospirosis is potentially a fatal zoonosis acquired by contact of skin and mucosal surfaces with soil and water contaminated with infected urine. We analyzed the outcome of infection of C3H/HeJ mice with Leptospira interrogans serovar Copenhageni using an enzootic mode of transmission, the conjunctival route. Infection led to weight loss and L. interrogans dissemination from blood to urine, and spirochetes were detected in blood and urine simultaneously. The infectious dose that led to consistent disseminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 36 publications
8
37
2
Order By: Relevance
“…We used Leptospira interrogans serovar Copenhageni strain Fiocruz L1-130 (henceforth Leptospira), culture passage 2 after hamster infection, originally isolated from a patient in Brazil. Leptospira was cultured as previously described [10] and enumerated by dark-field microscopy (Zeiss USA, Hawthorne, NY) that was confirmed by qPCR (StepOne Plus, Life Technologies, Grand Island, NY).…”
Section: Bacterial Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used Leptospira interrogans serovar Copenhageni strain Fiocruz L1-130 (henceforth Leptospira), culture passage 2 after hamster infection, originally isolated from a patient in Brazil. Leptospira was cultured as previously described [10] and enumerated by dark-field microscopy (Zeiss USA, Hawthorne, NY) that was confirmed by qPCR (StepOne Plus, Life Technologies, Grand Island, NY).…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…In this study, we used the C3H-HeJ sublethal model of leptospirosis to determine how exposure to L. interrogans serovar Copenhageni FioCruz L1-130 through the transdermal and oro-nasal routes of infection affect the timing of bacterial dissemination to blood and urine as well as the associated clinical outcomes and kidney pathology. Data are discussed taking into consideration our previous findings using the other route of natural infection, the ocular conjunctiva, CJ [10].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Eye drop inoculation is an interesting route of infection since it mimics a natural route of infection and is considered more physiological than intraperitoneal infection, which bypasses the natural defenses of the skin and mucosa. Recently, the Gomes-Solecki group showed in the C3H/HeJ TLR4 deficient mouse model that eye inoculation with 10 8 L. interrogans leads to acute leptospirosis with kidney lesions and colonization, although with a delay compared to the intraperitoneal route [46].…”
Section: How L Interrogans Establish Renal Chronicity?mentioning
confidence: 99%
“…Nevertheless, the intraperitoneal route of inoculation does not reflect the entrance of leptospires and the first phases of infection. Recently, a novel mouse model using sensitive C3H/HeJ mice infected through the conjunctival route of inoculation has shown that leptospires disseminate in blood, although with a delay compared to the intraperitoneal route, and provoke nephritis in the kidney, with glomerulus size reduction [18] . This novel model is interesting since it validates the peritoneal model.…”
Section: Pathophysiology Of Acute and Chronic Leptospirosis Focusing mentioning
confidence: 99%